Uso racional de antibióticos como práctica habitual, adecuada y evaluada por prescriptores médicos en el Hospital Regional de Loreto 2021 - Videira Paredes, Oswaldo (2023)
The present Project is carried out to find out if the medical staff of the Regional Hospital of Loreto, has as a habitual, adequate and evaluated practice the rational use of Antibiotics and thus avoid adverse events, cost reduction and bacterial resistance. In this sense, we want to evaluate whether the rationality of the use of antibiotics by prescribing medical personnel exists. The medical staff of the Hospitalization of Infectious Diseases and Internal Medicine service will be evaluated, since they are responsible for the prescription of antibiotics to be used in the patient, through a survey. The methodology to be used corresponds to an observational design, with a descriptive, cross-sectional and descriptive type of study, with simple Probabilistic sampling. With the results obtained, there would be a basis for the sustained and definitive implementation of the Hospital Antimicrobial Optimization Program. Providing better rational use, dose, route, duration, and avoid selection of resistant pathogens and adverse effects.